PENGARUH MANAJEMEN KUALITAS TERHADAP KINERJA USAHA MELALUI INOVASI PRODUK (Studi Usaha Kerupuk Sagu di Kabupaten Kuantan Singingi) - Apusma Wilda; Samsir Samsir; Daulay Nauly Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Quality Management (X) on Product Innovation (Y) and Business Performance (Z) of Kerupuk Sagu Business at Kuantan Singingi The population of study was 137 owners of Kerupuk Sagu Business and the samples were 102 people, it’s based on Slovin formula. Structural Equation Model (SEM) with SmartPLS version 3. was used as methods of data analysis. The results were: 1) Quality Management had a positive and significant effect on Product Innovation; 2) Quality Management had a positive and significant effect on Business Performance; 3) Product Innovation had a positive and significant effect on Business Performance; 4) Quality Management had a positive and significant effect on Business Performance throughwork Product Innovation.Keywords: Quality Management, Product Innovation, and Business Performance.